Sonographic evaluation of children with congenital hypothyroidism - Sedassari,Anelise de Almeida (2015)
Abstract Objective: To establish benchmarks and study some sonographic characteristics of the thyroid gland in a group of euthyroid children aged up to 5 years as compared with age-matched children with congenital hypothyroidism. Materials and Methods: Thirty-six children (17 female and 19 male) aged between 2 months and 5 years were divided into two groups – 23 euthyroid children and 13 children with congenital hypothyroidism – and were called to undergo ultrasonography. Results: In the group of euthyroid children (n = 23), mean total volume of the thyroid gland was 1.12 mL (minimum, 0.39 mL; maximum, 2.72 mL); a homogeneous gland was found in 17 children (73.91%) and 6 children (26.08%) had a heterogeneous gland. In the group of children with congenital hypothyroidism (n = 13), mean total volume of the thyroid gland was 2.73 mL (minimum, 0.20 mL; maximum, 11.00 mL). As regards thyroid location, 3 patients (23.07%) had ectopic thyroid, and 10 (69.23%) had topic thyroid, and out of the latter, 5 had a homogeneous gland (50%) and 5, a heterogeneous gland (50%). In the group with congenital hypothyroidism, 6 (46.15%) children had etiological diagnosis of dyshormoniogenesis, 3 (23.07%), of ectopic thyroid, and 4 (30.76%), of thyroid hypoplasia. Conclusion: Thyroid ultrasonography is a noninvasive imaging method, widely available, easy to perform and for these reasons could, and should, be performed at any time, including at birth, with no preparation or treatment discontinuation, to aid in the early etiological definition of congenital hypothyroidism.